PENGARUH PEMBIAYAAN TINGKAT UTANG PERUSAHAAN TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Priana, Zalfa Zafira; Maharani, Siti Laksmi (Transpublika Publisher, 2022)
Capital structure is a comparison between long-term debt to the company's capital. Every company aims to maximize the value of the company with the aim of maximizing the value of the company. Therefore, this study was conducted to determine the relationship between corporate debt on the company's performance on the IDX for five years. The independent variables in this study are Short term debt (STDA), Long term debt (LTDA), and Sales Growth (SG) while the dependent variables are Return on assets (ROA) and Net profit margin (NPM). This study uses small square regression and fixed and random effects models to analyze a cross-sectional sample of the food and beverage sector listed on the Indonesia Stock Exchange in the period 2016 - 2020 with a sample size of 19 companies. The results of the study will discuss whether short and Long term debt has an effect on company performance and whether Sales Growth has an effect on company performance.